Living Events: A Metaphor for Design - Mann, Richard Antony (Auckland University of Technology, 2009)
This thesis explores creativity and design by way of metaphor. It maps out the act of designing and considers dynamic forces that engender ways of living differently. Conception: The overall concept is for a book that articulates an extended metaphor through its volume, design and content. The metaphor targets all that is inexpressible about designing. It is an experimental and imaginative exercise that solves an ethics of encounter conducted through a micro-politics of daily activism. Milieu: The metaphor considers everyday situations and specific circumstances that are constituted by the actual occasions of designing. It explores the nexus at which designing is concentrated and traces outwards to determine the horizons of their milieu. Assemblage: The assemblage of the metaphor is the dynamic territory for creating, organizing and fitting together sensational and affective images of life-changing events. Account: The bound account of the metaphor forms visual and conceptual signs of designing into discussion and diagrams that negotiate the difficulty of both living and accounting for events. Dynamic: A cartographic approach surveys the image of the metaphor for indications of the problems that motivate its designing. Design: The design of the metaphor allows it to fold and unfold complexes of components that do not always connect directly but are always in communication with each other. Resolution: The metaphor crystallizes an image of a particulate instance of designing in which its binaries, living by design and designing by event, intersect.